2004
DOI: 10.1002/smj.417
|View full text |Cite
|
Sign up to set email alerts
|

Technological and product‐market experience and the success of new product introductions in the pharmaceutical industry

Abstract: The growth and development of a firm depend on its ability to introduce new products over time.To do this successfully, it requires technological knowledge, the ability to combine knowledge elements into valuable new products, and the complementary assets that facilitate the manufacturing, sales, and distribution of those products. We argue that these all develop as a function of a firm's experience in its technological and product-market domains. Moreover, given the prospect of complementarities among technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
363
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(389 citation statements)
references
References 77 publications
7
363
0
4
Order By: Relevance
“…Top managers of firms in high velocity environments also face high levels of competitive hostility; building sustainable competitive advantage is difficult because firms cannot protect existing products and processes for a long time (Eisenhardt and Martin, 2000;Fines, 1998;Williams, 1994) and, therefore, firms cannot sustain above-average profits based on a single established innovation or advantage. As top managers of firms in high velocity environments consistently address the fast changing, hostile, and unpredictable changes in the task sectors by introducing new products and/ or process technologies faster (Nerkar and Roberts, 2004;Cottrell and Nault, 2004) and carry out frequent strategic and organizational changes (Eisenhardt and Martin, 2000;Eisenhardt, 1989;Fines, 1998), task sector cues are likely to dominate subjective representations of their operating environment. In sum the stronger salience of task sector in high velocity environments is likely to result in greater dominance of task sector concepts in subjective representations of the environment, whereas the weaker salience of the task sector in low velocity environments will lead to lower levels of attention focus on task sector in managers' subjective representations.…”
Section: Industry Velocity and Attention Focusmentioning
confidence: 99%
See 3 more Smart Citations
“…Top managers of firms in high velocity environments also face high levels of competitive hostility; building sustainable competitive advantage is difficult because firms cannot protect existing products and processes for a long time (Eisenhardt and Martin, 2000;Fines, 1998;Williams, 1994) and, therefore, firms cannot sustain above-average profits based on a single established innovation or advantage. As top managers of firms in high velocity environments consistently address the fast changing, hostile, and unpredictable changes in the task sectors by introducing new products and/ or process technologies faster (Nerkar and Roberts, 2004;Cottrell and Nault, 2004) and carry out frequent strategic and organizational changes (Eisenhardt and Martin, 2000;Eisenhardt, 1989;Fines, 1998), task sector cues are likely to dominate subjective representations of their operating environment. In sum the stronger salience of task sector in high velocity environments is likely to result in greater dominance of task sector concepts in subjective representations of the environment, whereas the weaker salience of the task sector in low velocity environments will lead to lower levels of attention focus on task sector in managers' subjective representations.…”
Section: Industry Velocity and Attention Focusmentioning
confidence: 99%
“…The strategy literature has consistently prescribed the importance of aligning firm strategies with opportunities and threats in the environment (Andrews, 1987;Ginsberg, 1988;Miles and Snow, 1972;Mintzberg, 1972;Porter, 1985;Quinn, 1980;Hofer and Schendel, 1978). Further, research has demonstrated that firms that initiate timely strategic responses to changes in the environment outperform those that delay in their response (Cotrell and Nault, 2004;Haveman, 1992;Nerkar and Roberts, 2004;Smith and Grimm, 1987;Baum and Wally, 2003). Studies have also shown that firms that fail to adjust in a timely fashion may enter a downward spiral from which they do not escape (Cameron, Sutton, and Whetten, 1988;Hambrick and D'Aveni, 1988).…”
Section: The Mediating Role Of Attention Focus and Causal Logicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, search strategies related to the discovery of new knowledge are aligned with exploration, while those that address the learning of current knowledge are associated with exploitation. Despite differences in their objectives and outcomes, it is widely recognized that both types of strategy are needed in order for firms to enhance their innovation performance (March, 1991;Katila and Ahuja, 2002;Nerkar and Roberts, 2004;Laursen and Salter, 2006).…”
Section: Introductionmentioning
confidence: 99%